Australia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Australia. (IMF Staff Country Reports; Country Report, 2021)
Strong health and economic policies allowed for quick economic recovery from initial COVID-19-related lockdowns in 2020. Renewed outbreaks and lockdowns have created setbacks since mid-2021, with disproportionate impacts on some regions, sectors, and workers. Accommodative macroeconomic policies have been instrumental in cushioning the economic impact.